Survei Kepuasan Masyarakat Terhadap Ketersediaan Sarana Dan Prasarana Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Sidoarjo - Lu’luum Mahknunah; Ilmi Usrotin Choiriyah (Research Parks Publishers, 2021)
This study aims to determine the level of community satisfaction in the Population and Civil Registration Service at the Public Service Mall, Sidoarjo Regency. This research is a quantitative research. The sampling technique using the population is calculated using the Slovin formula. Research sample of 100 respondents consisting of service users. data collection techniques using a questionnaire. In this study, using 9 elements of community satisfaction survey indicators and data analysis techniques. The results showed that the level of service user satisfaction showed good performance. The achievement value this time is 3.39 with the achievement of all elements of service quality. There are two elements that are still below the average, namely requirements with an element value of 3.27, and facilities and infrastructure with an element value of 3.26. Services that get less value are a top priority consideration to improve service quality